Exploring the Benefits of Antioxidants in Dentistry: New Frontiers in Oral Care - Anuj Singh Parihar; Brahmananda Dutta; Diksha Yadav; M Sowmiya Narayanan; Tanu Sahney; Sharmila Nandamuri (Wolters Kluwer Medknow Publications, 2024)
In recent years, antioxidants have gained significant attention in the field of dentistry due to their potential therapeutic benefits in various dental conditions. This comprehensive review aims to provide a detailed analysis of the role of antioxidants in dentistry, focusing on their mechanisms of action, clinical applications, and future prospects. The review highlights the potential of antioxidants in preventing and managing oral diseases, promoting oral health, and enhancing the outcomes of dental treatments.